The complete bariatric surgery guide and diet program - Ekserci, Sue; Klein, Laz (Robert Rose Inc., 2022)
"Bariatric surgery is a procedure designed to help people decrease their food intake and change the way their body handles food - the result being significant weight loss. This new edition of The Complete Bariatric Surgery Guide and Diet Program provides up-to-date information on the many procedures that are currently available in North America, including vertical sleeve gastrectomy, duodenal switch and the Roux-en-Y gastric bypass. As important, it looks at the causes of obesity, obesity-related problems and standard treatments. All the potential risks and benefits associated with each type of bariatric surgery are examined, as well as measures of success, and preparation and recovery instructions. Because diet and lifestyle are integral to ensuring a successful bariatric surgical outcome, the second component of the book provides the resources for healthy eating, nutrition, supplements and making positive changes in lifestyle. To further ensure success, 150 recipes have been included that have been specially created with weight-loss patients in mind."--